Lupins foray into Japan - Jacob, Joshy; Agarwalla, Sobhesh Kumar, Premchander (London : SAGE Publications Ltd, 2017)
The case described the issues faced by a mid-sized Indian generic pharmaceutical firm, in its attempt to acquire a small unlisted Japanese generics manufacturer. It showcases the strong motivation of a successful emerging market pharmaceutical firm to expand into the developed market, buoyed by its cost competitiveness. The case presents an opportunity to discuss the trade-offs involved with most of the dynamic decisions in a cross-border acquisition, such as estimation of synergies and value, bidding, and financing the acquisition. The case may be used in programmes on valuation, and mergers and acquisitions.
Originally published: Jacobs, J., Agarwalla, S. K., & Premchander. (2012). Lupins foray into Japan. F&A0495. Ahmedabad: Indian Institute of Management, Ahmedabad.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Lupins; Pharmaceutical industry -- India -- Case studies; Consolidation and merger of corporations -- India -- Case studies